ChemInform Abstract: Facile Synthesis of 3‐Aryl‐3‐hydroxy‐2‐oxindoles from 2‐Arylindoles. Issue 47 (3rd November 2016) - Moon, Hye Ran; Lee, Sangku; Roh, Hwa Jung; Kim, Jae Nyoung
Abstract: An efficient synthetic route to 3‐aryl‐3‐hydroxy‐2‐oxindoles is developed from 2‐arylindoles via a semipinacol type rearrangement.